2000
DOI: 10.1017/s003329179900210x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-uterine physical growth in schizophrenia: evidence confirming excess of premature birth

Abstract: Our results suggest that prematurity at birth is associated with a risk of developing schizophrenia in adulthood. When gestational age and maternal body weight were allowed for, there was no evidence that schizophrenics tend to have lower mean BW or smaller BHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 39 publications
2
21
2
1
Order By: Relevance
“…An association between small head circumference at birth and the later development of schizophrenia was confirmed in a number of previous studies (Cantor-Graae et al, 1998;Hultman et al, 1999;Ichiki et al, 2000;Kunugi et al, 1996;McNeil et al, 2000). In accordance with our results, three of these studies showed a reduction in the risk related to small head circumference, after controlling for gestational age (Cantor-Graae et al, 1998;Kunugi et al, 1996;McNeil et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…An association between small head circumference at birth and the later development of schizophrenia was confirmed in a number of previous studies (Cantor-Graae et al, 1998;Hultman et al, 1999;Ichiki et al, 2000;Kunugi et al, 1996;McNeil et al, 2000). In accordance with our results, three of these studies showed a reduction in the risk related to small head circumference, after controlling for gestational age (Cantor-Graae et al, 1998;Kunugi et al, 1996;McNeil et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…We have found no relationship at all between head circumference at birth and in adulthood among patients with schizophrenia [11]. While five independent studies have found schizophrenia patients to have a significantly smaller head circumference at birth (typically in females) [11][12][13][14][15], other studies have found a disproportionately large head circumference in male schizophrenia patients in adulthood [11,16]. Beyond possible gender differences, these different results may reflect both normal and abnormal developmental phenomena.…”
Section: Stability Of This Antecedent Of Schizophreniacontrasting
confidence: 64%
“…On the basis of the present study, abnormalities in offspring can be attributed to either maternal treatment of dams with Poly I:C, and not to any disruptions in maternal immune response consequent to loss of NRG1. Gestational length in NRG1 HET was very slightly reduced (-3%) by maternal exposure to Poly I:C; some studies have reported that preterm birth is also a risk factor for schizophrenia (Ichiki et al, 2000;Vuillermot et al, 2010).…”
Section: Discussionmentioning
confidence: 95%